Praca nad emisją głosu i interpretacją dzieł muzycznych w zespole amatorskim. Wybrane zagadnienia na podstawie własnej pracy dyrygenckiej z Chórem Żeńskim "Melodia" = Work on voice emission and interpretation of musical works in an amateur band. Selected issues based on own conducting work with the "Melodia" Female Choir - Zeman, Aleksandra (Zielona Góra: Instytut Pedagogiki. Wydział Pedagogiki, Psychologii i Socjologii. Uniwersytet Zielonogórski)
This article deals with selected issues related to voice emission and interpretation of musical works in an amateur band. Work on correct voice emission is an extremely important area of a conductor's activity. It is essential for the correct way of operating the sung sound. It is an expression of the musical maturity of the choristers, as well as an inseparable element of a thoughtful interpretation of the works. Both the voice emission and the interpretation of the musical work must be treated as common ground.
Keywords: chór amatorski; dyrygent; emisja głosu; interpretacja dzieł chóralnych; amateur choir; conductor; voice emission; interpretation of choral works